Comparison of nanovesicles derived from Panax notoginseng at different size: physical properties, composition, and bioactivity - Chen, Xiaohang; Huang, Liyu; Zhang, Mengyuan; Lin, Shuoqi; Xie, Jing; Li, Hengyi; Wang, Xing; Lu, Youguang; Zheng, Dali (Frontiers in Pharmacology, 2024)
Aim: Plant-derived nanovesicles have emerged as potential agents for combating tumors. In this study, we investigated the inhibitory effects of Panax notoginseng-derived nanovesicles (PnNVs) on the proliferation and migration of squamous cell carcinoma. Additionally, we explored the relationship between plant tuber size and the physical properties, composition and bioactivity of these nanovesicles. Methods: We isolated PnNVs from Panax notoginseng tubers of varying sizes: small-sized (s_PnNVs), medium-sized (m_PnNVs) and large-sized (l_PnNVs), and evaluated for size, potential, and morphology. Cellular uptake efficiency was assessed using confocal microscopy and flow cytometry. The ability of different PnNVs to inhibit oral squamous cell carcinoma cells was evaluated using plate cloning, CCK8 assay, and scratch healing assay. Off-target metabolomics was used to compare metabolic compounds of different PnNVs. Results: Our findings revealed that s_PnNVs exhibited lower potential but had the highest cellular uptake efficiency, whereas m_PnNVs were characterized by the smallest size and lowest cellular uptake efficiency. Notably, m_PnNVs demonstrated the most effective inhibition of squamous cell carcinoma growth and migration. Compositional analyses showed that PnNVs were rich in proteins and contained lower levels of RNA, with l_PnNVs having the highest protein content. Furthermore, untargeted metabolomics analysis revealed a significant increase in the expression of specific antitumour-related metabolites in m_PnNVs compared to s_PnNVs and l_PnNVs. Conclusion: Overall, our results underscore the influence of plant tuber size on the bioactivity of the nanovesicles from which they are derived, emphasizing its importance for experimental design and study reproducibility.